1992
DOI: 10.1159/000267140
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating Lymphocytes and Antigen Expression in Uveal Melanoma

Abstract: Monoclonal antibodies and flow cytometry were used to study lymphocyte, monocyte and tumor cell antigen expression in uveal melanoma. Forty-one melanomas were studied after various forms of treatment. An antimelanoma antibody, 13A3E, stained 81.7% of the cells. Tumors treated with helium ions or l25I plaques had 13A3E staining reduced to 62.5%, p = 0.011. HLA-ABC stained 85.4%, and HLA-DR stained 7.0% of the cells. T cells (CD3 positive) comprised 4.5 % (range 0.1–29.2 %) of total cell population. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
1
29
3
Order By: Relevance
“…Tumor infiltrating lymphocytes have been detected in variable proportions in UMM (30,37), with either a predominance ofCD3+/CD8+ cells or CD4+ and CD8+ cells present in equal amounts (27,30) or a predominance of CDI6+ NK cells (29). Ma and co-workers (38) showed that, during the early stage of tumor growth, CD4+ cells were the dominant T cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor infiltrating lymphocytes have been detected in variable proportions in UMM (30,37), with either a predominance ofCD3+/CD8+ cells or CD4+ and CD8+ cells present in equal amounts (27,30) or a predominance of CDI6+ NK cells (29). Ma and co-workers (38) showed that, during the early stage of tumor growth, CD4+ cells were the dominant T cell population.…”
Section: Discussionmentioning
confidence: 99%
“…The effective role of tumor-infiltrating lymphocytes (TIL) in biological behavior of UMM is still far from being clarified (3,13, IS, [27][28][29]. There is, to date, no convincing evidence that a better prognosis is associated with lymphocytic infiltration in UMM (15,(30)(31).…”
mentioning
confidence: 99%
“…A large immunohistochemical study showed that 134 out of 1,078 tumors contained a lymphocytic infiltrate (100 or more lymphocytes per 20 high-power (×400) microscopic fields) [9]. A second study of 27 tumors showed that lymphocyte infiltration is variable when tumor suspensions were analyzed by flow cytometry and a substantial proportion of TIL were CD8+ T cells, with some CD4+ T cells [10]. These subpopulations were respectively named T suppressor/cytotoxic T lymphocytes (CTL) and helper T cells, but they were not functionally assessed.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…In one study TIL were predominantly CD8+ T cells,22 in another study CD4 + and CD8+ cells were present in equal amounts, 23 and in yet another report CD16+ natural killer (NK) cells were the dominant lympho cyte population, accounting for 41 % of the TIL. 24 The prognostic significance of TIL in uveal melano mas is also unclear.…”
Section: Role Of Intraocular Tumour Infiltrating Lymphocytesmentioning
confidence: 95%